Pelatihan Inovasi Pembuatan Produk Minuman Kepada Siswa-Siswi SMA Maitreyawira Kota Batam Provinsi Kepulauan Riau - Wahyudi Ilham; Steven Johnson; Bram Handoko (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
The training on innovation in beverage product creation for students of SMK Maitreyawira in Batam City, Riau Islands Province, aims to enhance students' skills and knowledge in entrepreneurship, particularly in the beverage industry. This activity includes providing materials on the concept of innovation, techniques for making attractive and high-value beverages, and hands-on practice in making various types of beverages. Through this training, students are expected to develop their ability to innovate and create unique beverage products with market potential. The results of the training show an increase in students' understanding and skills in making beverage products, as well as growing interest in the field of entrepreneurship. It is hoped that this activity will positively impact students' readiness to enter the workforce and open new business opportunities in the future.